Caracterização e diferenciação morfológica e funcional da placa dentária dos representantes da família Potamotrygonidae (Elasmobranchii: Myliobatiformes) - Lima, Danilo Pinto (2025)
The family Potamotrygonidae consists of a unique group of Neotropical stingrays. It includes two subfamilies composed of a few marine species, and the only well-established lineage of freshwater stingrays. The group comprises forty valid species distributed across most river basins that flow into the Atlantic Ocean, except for a few parts of northeastern, southeastern, and southern Brazil. Although the group is well known by local communities and the aquarium trade, the phylogenetic relationships among its species are complex, and several divergent hypotheses have been proposed. In this context, data on internal and external anatomy are scarce or poorly explored, and information on dental morphology within the group is limited or absent. Likewise, data on feeding habits and their relationship with dental morphology are also scarce. Therefore, the present study aims to conduct a morphological and comparative description of the dental plate of representatives of the family Potamotrygonidae, to optimize the proposed dental characters in a combined phylogenetic tree to understand their evolution within the group, and to correlate the identified dental characters with known feeding habits reported in the literature. A total of 42 specimens representing 21 species were examined. The dental plates were removed using dissection tools, and the specimens were analyzed using micro-CT scanning and a stereomicroscope. 54 morphological characters were identified, and a combined phylogenetic analysis including molecular data was conducted. A literature review of feeding habits was also performed, and this information was correlated with the dental morphology through a historical reconstruction on the resulting phylogenetic tree. The phylogenetic analysis supports some previously proposed relationships, revealing two main clades within Potamotrygoninae: one composed of Heliotrygon and Paratrygon + Plesiotrygon, and Potamotrygon, with the possibility that Potamotrygon is paraphyletic without the inclusion of Plesiotrygon. The historical reconstruction of feeding habits indicated that Heliotrygon and Paratrygon exhibit specializations toward an adapted morphology to piscivory, that species such as Potamotrygon jabuti and Potamotrygon motoro are more adapted to consuming harder prey, and most Potamotrygonines show adaptations for crushing prey.